Dasar Filosofi Marketing Syari’ah - Moh. Muzwir Luntadjo (IAIN Manado, 2009)
Syariah marketing is an business process which the was entirety of process of applying Islam values. Any way how to make business process placing forward justice values and sincerity. Syari’ah marketing is a strategic business discipline which instruct creation process, offer, and change of value from an inisiator to stakeholder, which in all the process of as according to elementary principles and akad [of] muamalah (bisnis) in Islam. Especial Elementary in application of Syariah marketing is all fundamental theorems concerning business of Islam, what included in Al Holy, Hadis Prophet, and also various moslem scholar religious advices.